Quality of Life and Mental Health of Infertile Women Affected by Endometriosis: A Narrative Review - Zarbo, Cristina; Brugnera, Agostino; Secomandi, Rita; Candeloro, Ilario; Malandrino, Chiara; Betto, Enrico; Bellia, Adriano; Rabboni, Massimo; Bondi, Emi; Frigerio, Luigi; Compare, Angelo (Current Women's Health Reviews, 2019)
Objective: Infertility has a severe impact on quality of life and mental health. This condition could be exacerbated by the existence of comorbid medical disease, like endometriosis. The aim of this critical narrative review is the examination of the state of the art about the quality of life and mental health in infertile women with endometriosis. Methods: We performed a rigorous and systematic search for studies on multiple electronic databases. A total of 6 papers were included in the review and were subjected to interpretative and critical narrative synthesis. Results and Discussion: Major findings are resumed in the following points: (a) infertile women with endometriosis when compared to infertile ones without endometriosis show higher depression, stress perception, and anxiety, and lower general quality of life; (b) quality of life specifically related to infertility is similar among women with and without endometriosis and seems to be related to personality and beliefs factors; (c) giving birth to a child is related to better mental quality of life; (d) during assisted reproductive treatment (ART) stimulation, infertile women with endometriosis have a decrease of dysmenorrhea and dyspareunia; (e) satisfaction of ART is related to the number of attempts, treatment accomplishment and pregnancy test outcomes. Clinical implications of these findings and suggestions for future researches were discussed. Conclusion: Concluding, it is crucial to assess the psychological factors related to endometriosis and infertility to reduce the impact of these diseases on quality of life and mental health, provide adequate support to these patients, improve their satisfaction and increase the change to get pregnant.
Keywords: quality of life